Perbandingan Hukum Pembubaran Partai Politik Jerman dan Indonesia - Nadzirotus Sintya Falady (Jurnal Ilmiah Penegakan Hukum, 2020)
The objective of this article is to analyze the mechanism of dissolution political parties in Germany in order to find the right policy of dissolution political parties in Indonesia. Normative juridical research methods are used in this study with case studies and comparative approaches. The data source used is the secondary data source, which consists of primary legal material, secondary legal material, and tertiary legal material. This research analyzed descriptively qualitative. The conclusion obtained is that the dissolution of political parties denied the right of association and assembly which is endorsed by the constitution. The German Constitutional Court has disbanded political parties proportionally by examining and deciding on the dissolution of political parties not only in text but also in the context which meets the criteria of  ”clear and present danger” to the sovereignty of the German Federal Government and the free democratic basic order. Therefore, it is necessary to redesign the disruption of the dissolution of political parties in Indonesia with empirical sociological and psychological studies in order to meet the ”clear and present danger” criteria